1994
DOI: 10.1007/bf01499172
|View full text |Cite
|
Sign up to set email alerts
|

Default values in eyewitness descriptions: A problem for the match-to-description lineup foil selection strategy.

Abstract: Study 1 (N = 205) reveals that witnesses often provide vague descriptions. Witnesses leave out information such as sex and race that they certainly noticed (default values). Study 2 (N = 89) weakly supports the claim (Luus & Wells, 1991) that correct identification rates from lineups are enhanced by selecting foils who fit the description of the criminal rather than foils who are highly similar to the suspect. Study 3 (N = 210) indicates that false identification rates can be inflated by selecting lineup foils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(126 citation statements)
references
References 15 publications
10
112
4
Order By: Relevance
“…In light of these circumstances, it is important to consider the potential impact of providing descriptions of several individuals seen within a similar encoding context. Despite the fact that descriptions of faces are often vague and imprecise (Ellis et al, 1980;Lindsay, Martin, & Webber, 1994) and that some authors have suggested that providing descriptions may interfere with subsequent identification (e.g., Brown & Lloyd-Jones, 2003), the present experiments show that providing descriptions of multiple faces can benefit their subsequent recognition. Furthermore, constraining witnesses to describe faces in a particular way-for instance, by focusing on holistic aspects of the face-may increase this benefit.…”
Section: Facilitation Versus Interferencecontrasting
confidence: 48%
“…In light of these circumstances, it is important to consider the potential impact of providing descriptions of several individuals seen within a similar encoding context. Despite the fact that descriptions of faces are often vague and imprecise (Ellis et al, 1980;Lindsay, Martin, & Webber, 1994) and that some authors have suggested that providing descriptions may interfere with subsequent identification (e.g., Brown & Lloyd-Jones, 2003), the present experiments show that providing descriptions of multiple faces can benefit their subsequent recognition. Furthermore, constraining witnesses to describe faces in a particular way-for instance, by focusing on holistic aspects of the face-may increase this benefit.…”
Section: Facilitation Versus Interferencecontrasting
confidence: 48%
“…For example, we are currently testing how well lineup fairness measures can detect variations in lineup fairness (i.e., two or five fillers that match the target's description). Future research could also take a more systematic approach when examining the correspondence between descriptions and lineup members, such as measuring or varying the prototypicality of lineup member's features to determine whether this factor affects lineup fairness (e.g., Lindsay, Martin, & Webber, 1994). For example, if the description indicates the perpetrator was blond, are mock witnesses less likely to select a lineup member with dirty blond hair than one with platinum blond hair?…”
Section: Future Researchmentioning
confidence: 99%
“…We also expect those with ID to have poorer understanding of the purpose of a lineup task, be less likely to remember that the perpetrator may or may not be present, and be less likely to demonstrate an association between confidence and lineup accuracy. The lineups used in the present experiment have been used in previous published research (Wilcock et al 2005; and were developed using a match to description of culprit using a procedure based on that used by Lindsay, Martin, and Webber (1994). The perpetrator present lineups contained the perpetrator and five foils.…”
Section: Instructions Given To Witnesses Prior To Them Viewing An Idementioning
confidence: 99%